Fibras de sisal (Agave sisalana) como isolante térmico de tubulações - Neira, Dorivalda Santos Medeiros (2005)
In the last decades there was a significant increasing of the numbers of researchers that joint efforts to find alternatives to improve the development of low environmental impact technology. Materials based on renewable resources have enormous potentials of applications and are seen as alternatives for the sustainable development. Within other parameters, the sustainability depends on the energetic efficiency, which depends on the thermal insulation. Alternative materials, including vegetal fibers, can be applied to thermal insulation, where its first goal is to minimize the loss of energy. In the present research, it was experimentally analyzed the thermal behavior of fiber blankets of sisal (Agave sisalana) with and without surface treatment with oxide hidroxide (NaOH). Blankets with two densities (1100/1200 and 1300/1400 g/m2) were submitted to three rates of heat transfer (22.5 W, 40 W and 62.5 W). The analysis of the results allowed comparing the blankets treated and untreated in each situation. Others experiments were carried out to obtain the thermal conductivity (k), heat capacity (C) and the thermal diffusivity (α) of the blankets. Thermo gravimetric analyses were made to the verification of the thermal stability. Based on the results it was possible to relate qualitatively the effect of the heat transfer through the sisal blankets subjected to three heat transfer rates, corresponding to three temperature values (77 °C, 112 °C e 155 °C). To the first and second values of temperature it was verified a considerable reduction on the rate of heat transfer; nevertheless, to the third value of temperature, the surface of the blankets (treated and untreated) in contact with the heated surface of the tube were carbonized. It was also verified, through the analyses of the results of the measurements of k, C e α, that the blankets treated and untreated have values near to the conventional isolating materials, as glass wool and rock wool. It could be concluded that is technically possible the use of sisal blankets as constitutive material of thermal isolation systems in applications where the temperature do not reach values greater than 112 ºC